Techniques to modify cluster architecture and their effect on the viticultural performance of the Sauvignon Blanc cultivar - Brighenti, Alberto Fontanella; Munhoz, Bruno; Würz, Douglas André; Pasa, Mateus da Silveira; Pinto, Felipe Augusto Moretti Ferreira; Araújo Filho, Jerônimo Vieira de; Silva, Aparecido Lima da (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to evaluate the effect of different techniques to modify grape cluster architecture on the incidence and severity of botrytis bunch rot, as well as on the viticultural performance of the 'Sauvignon Blanc' grapevine (Vitis vinifera). Associated with fungicides, four treatments were tested: control, 30 ppm gibberellic acid sprayed at full bloom, 1,000 ppm prohexadione calcium sprayed at full bloom, and berry thinning at the stage of beginning of berry touch. The experiment was carried out in the 2015, 2016, and 2017 vintages. Clusters were treated with fungicides during the stages of full bloom, beginning of berry touch, veraison, and around 15 days before harvest. Berry thinning does not cause losses in the yield and quality of 'Sauvignon Blanc', and, despite having little effect on cluster architecture, is effective in reducing the incidence and severity of Botrytis cinerea. Prohexadione calcium improves grape phenolic maturation, is effective in reducing the incidence and severity of B. cinerea, and reduces cluster compactness by decreasing berry diameter. The application of gibberellic acid spray at full bloom is not recommended because it decreases yield and bud fertility and increases berry susceptibility to B. cinerea infection.